Referential Values of Testicular Volume Measured by Ultrasonography in Normal Children and Adolescents: Z-Score Establishment - Liu, Chen; Liu, Xiao; Zhang, Xiangxiang; Yang, Boyang; Huang, Lan; Wang, Hongying; Yu, Hongkui (Frontiers in Pediatrics, 2021)
Objective: To establish Z-score regression equation derived from age for testicular volume measured by ultrasonography in normal boys aged 0 to18 years old. Method: The length (L), width (W), and height (H) of 3328 testicles from 1664 Chinese boys were measured by ultrasonography. Lambert's formula: L×W×H×0.71 was used to calculate testicular volume. Z-score regression equation derived from age was established by regression analysis of predicted values of testicular volume and standard deviations. Result: There was no significant difference between left and right testicular volumes. Testicular volume was positively correlated with age, and logarithmic transformation of testicular volume can show a fine curve fit with age. To establish Z-score regression equation derived from age, the predicted values of testicular volume used cubic regression equations, and the standard deviation used square regression equations. The Z-score regression equation derived from age was calculated by the formula: z = (lg (L×W×H×0.71) - (-0.3524-0.01759×x+0.009417×x2-0.0001840 ×x3)) / (0.1059+0.01434×x-0.0005324×x2). Conclusion: The current study provided a reference value for testicular volume of boys aged 0 to 18 years old. Z-score regression equation derived from age for testicular volume can be established. Z-score will be of great value for the testicular development assessment and disease diagnosis and follow-up.